Penyuluhan Dampak Minuman Alkohol Pada Remaja di Keluarahan Koya Kecamatan Tondano Selatan - Threesje Tolukun (Peneliti.net, 2020)
This community service program is carried out and focuses on education and provides counseling to adolescents who drink alcohol in the Koya sub-district, South Tondano District. Because young people as the next generation are still many who do not realize that drinking alcohol can damage the human body and damage the way of thinking of adolescents and the way of acting of adolescents, by providing counseling to adolescents it can reduce delinquency committed by adolescents by providing counseling. Because the impact of drinking alcohol on adolescents is very detrimental to future life, it is hoped that in the process of providing counseling they will gain knowledge and understanding for adolescents to be able to change attitudes and realize that drinking alcohol is detrimental and damaging to their future. After being given counseling from 24 teenagers who attended the counseling a few weeks later the extension officers evaluated it through interviews with the surrounding community, there were still 3 teenagers who still drank alcohol but did not get drunk again or excessively. So the extension worker concluded that the counseling given to teenagers in the Koya sub-district, Tondano Selatan sub-district was successful.